Laboratory measurement of the anticoagulant activity of edoxaban: a systematic review - Cuker, Adam (J Thromb Thrombolysis, 2015)
Edoxaban, an oral direct inhibitor of factor Xa, was recently approved in the United States and Japan for prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation and for treatment of venous thromboembolism (VTE). It is also licensed in Japan for prevention of VTE after major orthopedic surgery. Although routine laboratory monitoring of edoxaban is not required, laboratory measurement may be desirable in special circumstances. Our objective was to provide a systematic review of current evidence on laboratory measurement of the anticoagulant activity of edoxaban. PubMed and the Cochrane Library were searched for studies that reported a relationship between coagulation tests and plasma edoxaban levels. Study quality was assessed using Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2). We identified 9 eligible studies. Anti-Xa activity is linear across a broad range of drug levels (R(2)>0.95) and may be used for edoxaban quantification. The assay shows greater variability at above on-therapy drug concentrations. The PT is less sensitive to edoxaban. A normal prothrombin time may not exclude clinically relevant on-therapy drug levels. The activated partial thromboplastin time has insufficient sensitivity to edoxaban for measurement of its anticoagulant activity. Edoxaban exhibits variable effects on coagulation assays. Understanding these effects facilitates interpretation of test results in edoxaban-treated patients. More data on the relationship between drug levels, coagulation test results, and clinical outcomes in patients are needed.